Manual of botulinum toxin therapy - Dressler, Dirk; Hallett, Mark 1943-; Pathak, Mayank; Truong, Daniel; Zachary, Christopher B. (Cambridge University Press, 2024)
Providing practical, visually oriented guidance on the benefits of botulinum toxin in a wide variety of disorders, some new and unexpected, this new edition of Manual of Botulinum Toxin Therapy is fully updated in scope and detail. Chapters discuss the pathophysiology of each condition, summarizing the rationale for botulinum toxin, and describing the injection approach. Clear illustrations of the injection sites are included, using a 'clinician's eye' perspective, which allows physicians to readily identify anatomical landmarks and approach angles for injection. Dosing tables for available toxin formulations are included. The Manual covers cosmetic treatment of the upper and lower face, as well as aesthetic smile correction. Extensive guidance on how to use ultrasound and how cadaveric dissections can assist localization and targeting of injections is provided. Designed for teaching and bedside guidance, the Manual is useful to a diverse range of clinicians looking to use botulinum toxin in their practice.